Rotating Monitoring System and Multi-Model Evaluation for Enhancing Islamic Religious Education Extracurricular Quality in Elementary Schools - Maida, Hanik Rista; Khoiruddin, Heri (Tahta Media Group, 2025)
This study aims to comprehensively analyze the implementation of monitoring and evaluation of Islamic Education extracurricular activities at SDN 5 Jurug, Sooko District, Ponorogo Regency, with a focus on: (1) the monitoring procedures applied by Islamic Education teachers in supervising six religious extracurricular programs; (2) the evaluation model used and its effectiveness; (3) supporting and inhibiting factors in the implementation of monitoring and Evaluation. The research used a qualitative approach with a field study method involving one Islamic Education teacher as the main participant. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing, with data validity ensured through source and method triangulation. The results of the study show that SDN 5 Jurug implements a two-way monitoring system (directly through teachers on duty with a rotation schedule, and indirectly through attendance records) and implements four evaluation models simultaneously (Summative Evaluation, Goal-Oriented Evaluation Model, Countenance Evaluation Model, and Ten-Step Evaluation Model). The main supporting factors include full support from the principal, availability of adequate facilities, involvement of competent external mentors, and active participation of parents. The identified inhibiting factors are the lack of awareness and commitment of some teachers on duty to the established monitoring schedule. This study concludes that the integration of a rotation monitoring system and multi-model Evaluation has proven effective in improving the quality of religious extracurricular programs. However, improvements are needed in terms of the consistency of supervising teachers' attendance to achieve optimal results.